Hematological values and anatomopathological lesions in white leghorn hens affected by chronic respiratory disease - Colas C., Manuel (2016)
The chronic respiratory disease (CRD) is considered as an infectocontagious disease of multiple etiology that causes great economic losses in poultry farming. The clinical signs and lesions in affected animals can be severe when mixed infections occur. In Cuba this respiratory complex is evident; however, it is not known how the hemathological values vary in affected fowls. The objective of this study was to determine the hemathological values and anatomopathological lesions in CRD affected White Leghorn hens. A total of 34 hens of 32 weeks of age were sampled in an affected flock (17 affected and 17 healthy) and was conducted the clinical evaluation, necropsy, isolation and identification of bacteria and hematological analysis. The frequencies of microorganisms and lesions present, as well as means of hematological variables between ill and healthy birds were compared. The presence of Ornithobacterium rhinotracheale, Mycoplasma gallisepticum and Escherichia coli were evidenced alone or in mixed infections (5.935.3%). Main lesion observed were catarrhal tracheitis (76.5%), genital atrophy (52.9%), airsacculitis (47.1%), fibrinous rhinoconjunctivitis and hepatic alterations (41.2%) (p<0.05). The hematological analysis showed lower values of hemoglobin (8.9 g/dl), hematocrit (29.7%) and total leukocytes (9.9×103/mm3) with increase of heterophils (18.2%) in ill animals in comparison with the healthy ones. It is concluded that in CRD affected fowls respiratory lesions are predominant and hematological values are affected.